Glucocorticoids and Cancer - Pufall, Miles A. (Adv Exp Med Biol, 2015)
Unlike other steroid hormone receptors, the glucocorticoid receptor (GR) is not considered an oncogene. In breast cancer, the estrogen receptor (ER) drives cell growth, proliferation, and metastasis, and the androgen receptor (AR) plays a similar role in prostate cancer. Accordingly, treatment of these diseases has focused on blocking steroid hormone receptor function. In contrast, glucocorticoids (GCs) work through GR to arrest growth and induce apoptosis in lymphoid tissue. Glucocorticoids are amazingly effective in this role, and have been deployed as the cornerstone of lymphoid cancer treatment for decades. Unfortunately, not all patients respond to GCs and dosage is restricted by immediate and long term side effects. In this chapter we review the treatment protocols that employ glucocorticoids as a curative agent, elaborate on what is known about their mechanism of action in these cancers, and also summarize the palliative uses of glucocorticoids for other cancers.